Johnny Tremain - Forbes, Esther (New York : Dell, 1969)
After injuring his hand, a silversmith's apprentice in Boston becomes a messenger for the Sons of Liberty in the days before the American Revolution
Keywords: Newbery Medal -- 1944; Newbery Medal; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction